The rise of the Pasdaran : assessing the domestic roles of Iran's Islamic Revolutionary Guards Corps - Wehrey, Frederic; National Defense Research Institute (Rand Corporation); United States. Dept. of Defense. Office of the Secretary of Defense
Examines the broad-ranging domestic roles of Iran's Islamic Revolutionary Guards Corps, assessing its influence over Iran's political culture, economy, and society and its ability to shape the political future of the Islamic Republic of Iran. Iran's Islamic Revolutionary Guards Corps (IRGC) — also known as the Pasdaran (Persian for “guards”) — was initially created by Ayatollah Khomeini during the 1978–1979 Islamic Revolution as an ideological guard for the nascent regime. Since then, it has evolved into an expansive socio-political-economic conglomerate whose influence extends into virtually every corner of Iranian political life and society. In the political sphere, many high-ranking officials are former Pasdaran. As a force in Iranian culture and society, the IRGC controls media outlets and conducts training and education programs that are designed not only to bolster loyalty to the regime and train citizens in homeland defense, but also to improve the IRGC's own institutional credibility. And on the economic front, the IRGC controls a wide variety of commercial enterprises, including both government contracting and illicit smuggling and black-market enterprises. In this monograph, Wehrey et al. assess the IRGC less as a traditional military entity and more as a domestic actor, emphasizing its multidimensional nature and the variety of roles it plays in Iran's political culture, economy, and society.